Daratumumab and antineoplastic therapy versus antineoplastic therapy only for adults with newly diagnosed multiple myeloma ineligible for transplant - Langer, Peter; John, Lukas; Monsef, Ina; Scheid, Christof; Piechotta, Vanessa; Skoetz, Nicole (The Cochrane database of systematic reviews, 2024)
BACKGROUND: Multiple myeloma (MM) is a haematological malignancy that is characterised by proliferation of malignant plasma cells in the bone marrow. For adults ineligible to receive high-dose chemotherapy and autologous stem cell transplant, the recommended treatment combinations in first-line therapy generally consist of combinations of alkylating agents, immunomodulatory drugs, and proteasome inhibitors. Daratumumab is a CD38-targeting, human IgG1k monoclonal antibody recently developed and approved for the treatment of people diagnosed with MM. Multiple myeloma cells uniformly over-express CD-38, a 46-kDa type II transmembrane glycoprotein, making myeloma cells a specific target for daratumumab. - OBJECTIVES: To determine the benefits and harms of daratumumab in addition to antineoplastic therapy compared to antineoplastic therapy only for adults with newly diagnosed MM who are ineligible for transplant. - SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, EU Clinical Trials Register, ClinicalTrials.gov, WHO ICTRP, and conference proceedings from 2010 to September 2023. - SELECTION CRITERIA: We included randomised controlled trials that compared treatment with daratumumab added to antineoplastic therapy versus the same antineoplastic therapy alone in adult participants with a confirmed diagnosis of MM. We excluded quasi-randomised trials and trials with less than 80% adult participants, unless there were subgroup analyses of adults with MM. - DATA COLLECTION AND ANALYSIS: Two review authors independently screened the results of the search strategies for eligibility. We documented the process of study selection in a flowchart as recommended by the PRISMA statement. We evaluated the risk of bias in included studies with RoB 1 and assessed the certainty of the evidence using GRADE. We followed standard Cochrane methodological procedures. - MAIN RESULTS: We included four open-label, two-armed randomised controlled trials (34 publications) involving a total of 1783 participants. The ALCYONE, MAIA, and OCTANS trials were multicentre trials conducted worldwide in middle- and high-income countries. The AMaRC 03-16 trial was conducted in one high-income country, Australia. The mean age of participants was 69 to 74 years, and the proportion of female participants was between 40% and 54%. All trials evaluated antineoplastic therapies with or without daratumumab. In the ALCYONE and OCTANS trials, daratumumab was combined with bortezomib and melphalan-prednisone. In the AMaRC 03-16 study, it was combined with bortezomib, cyclophosphamide, and dexamethasone, and in the MAIA study, it was combined with lenalidomide and dexamethasone. None of the included studies was blinded (high risk of performance and detection bias). One study was published as abstract only, therefore the risk of bias for most criteria was unclear. The other three studies were published as full texts. Apart from blinding, the risk of bias was low for these studies. Overall survival Treatment with daratumumab probably increases overall survival when compared to the same treatment without daratumumab (hazard ratio (HR) 0.64, 95% confidence interval (CI) 0.53 to 0.76, 2 studies, 1443 participants, moderate-certainty evidence). After a follow-up period of 36 months, 695 per 1000 participants survived in the control group, whereas 792 per 1000 participants survived in the daratumumab group (95% CI 758 to 825). Progression-free survival Treatment with daratumumab probably increases progression-free survival when compared to treatment without daratumumab (HR 0.48, 95% CI 0.39 to 0.58, 3 studies, 1663 participants, moderate-certainty evidence). After a follow-up period of 24 months, progression-free survival was reached in 494 per 1000 participants in the control group versus 713 per 1000 participants in the daratumumab group (95% CI 664 to 760). Quality of life Treatment with daratumumab may result in a very small increase in quality of life after 12 months, evaluated on the EORTC QLQ-C30 global health status scale (GHS), when compared to treatment without daratumumab (mean difference 2.19, 95% CI -0.13 to 4.51, 3 studies, 1096 participants, low-certainty evidence). The scale is from 0 to 100, with a higher value indicating a better quality of life. On-study mortality Treatment with daratumumab probably decreases on-study mortality when compared to treatment without daratumumab (risk ratio (RR) 0.72, 95% CI 0.62 to 0.83, 3 studies, 1644 participants, moderate-certainty evidence). After the longest follow-up available (12 to 72 months), 366 per 1000 participants in the control group and 264 per 1000 participants in the daratumumab group died (95% CI 227 to 304). Serious adverse events Treatment with daratumumab probably increases serious adverse events when compared to treatment without daratumumab (RR 1.18, 95% CI 1.02 to 1.37, 3 studies, 1644 participants, moderate-certainty evidence). After the longest follow-up available (12 to 72 months), 505 per 1000 participants in the control group versus 596 per 1000 participants in the daratumumab group experienced serious adverse events (95% CI 515 to 692). Adverse events (Common Terminology Criteria for Adverse Events (CTCAE) grade ≥ 3) Treatment with daratumumab probably results in little to no difference in adverse events (CTCAE grade ≥ 3) when compared to treatment without daratumumab (RR 1.01, 95% CI 0.99 to 1.02, 3 studies, 1644 participants, moderate-certainty evidence). After the longest follow-up available (12 to 72 months), 953 per 1000 participants in the control group versus 963 per 1000 participants in the daratumumab group experienced adverse events (CTCAE grade ≥ 3) (95% CI 943 to 972). Treatment with daratumumab probably increases the risk of infections (CTCAE grade ≥ 3) when compared to treatment without daratumumab (RR 1.52, 95% CI 1.30 to 1.78, 3 studies, 1644 participants, moderate-certainty evidence). After the longest follow-up available (12 to 72 months), 224 per 1000 participants in the control group versus 340 per 1000 participants in the daratumumab group experienced infections (CTCAE grade ≥ 3) (95% CI 291 to 399). - AUTHORS' CONCLUSIONS: Overall analysis of four studies showed a potential benefit for daratumumab in terms of overall survival and progression-free survival and a slight potential benefit in quality of life. Participants treated with daratumumab probably experience increased serious adverse events. There were likely no differences between groups in adverse events (CTCAE grade ≥ 3); however, there are probably more infections (CTCAE grade ≥ 3) in participants treated with daratumumab. We identified six ongoing studies which might strengthen the certainty of evidence in a future update of this review.
Gesehen am 10.04.2025